Human Resources Needs for Medical Records Officers at the Mataram City Health Center - Syamsuriansyah, Syamsuriansyah; Hizriyansyah, Hizriyansyah; Ariffin, Nik Azliza Nik; Putra, Rizal Pratama Adi (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
Human resources are the most important and integral part of any organization, including the health sector. Therefore, this study aimed to examine human resources needs in the medical records field, with a particular focus on the roles and responsibilities of medical records officers. The analysis was carried out to identify critical challenges faced by medical record officers in meeting health service standards and managing patient data. Secondary data were collected from a survey of workload and human resources needs for medical records in 2023. The samples were selected using the Stratified Sampling method, by dividing the population into two groups (strata) based on the accreditation levels of health centers in Mataram city. Specifically, Tanjung Karang represented the main accredited center, while Babangan was categorized as a basic accredited center. Data analysis was performed with the Workload Indicators of Staffing Need Method (WISN) to calculate labor requirements and health crew members necessary for evaluating the distribution of health worker availability. The results showed the scarcity of medical record officers, difficulties in managing patient data, as well as the need for training and skills development in line with advances in information technology within the health sector.